Guggulipid: A Promising Multi-Purpose Herbal Medicinal Agent - Ahmad, Md Afroz; Mujeeb, Mohd; Akhtar, Mohd; Khushtar, Mohd.; Arif, Mohd.; Haque, Md Rafiul (Drug Research, 2020)
Herbal medicines therapy is appreciated by many research works because herbal drugs have relatively high therapeutic window, lower side effects and more cost effective. Guggulipid is an ethyl acetate extract of resin known as guggul from the tree Commiphora wightii / mukul (Arn.) Bhandari. Chemical analysis revealed that the compounds responsible for the major activities of gum guggul are the isomers E- and Z-guggulsterone. Guggul has been used for thousands of years in the treatment of arthritis, inflammation, obesity, cardiac protection, anti-ulcer, anti-epileptic and disorders of lipid metabolism. This review is an assortment of available information reported on its chemical, pharmacological and toxicological properties in various research studies. The available therapeutic properties of guggulipid make it suitable natural product for the treatment of various disorders like inflammation, pain, wounds, liver disorder and Acne etc. Graphical Abstract Graphical Abstract.
Keywords: cardiovascular diseases; central nervous system disorders; anticoagulant/thrombolytic drugs